Modified Cipher Feedback Mode based on a Dynamic Hénon Map Key for Image Data Security - Naufal Zafrany Syamsudin; Nur Rochmah Dyah Puji Astuti (Universitas Islam Indragiri, 2026)
The security of digital image transmission is vulnerable to statistical analysis attacks due to the high spatial correlation among pixels. In addition, the implementation of chaotic systems on digital devices often suffers from periodic degradation problems. To address these issues, this study proposes a modified Cipher Feedback (CFB) mode integrated with a dynamic key generator based on the Hénon Map. The main contribution of this research lies in the use of SHA-256 hashing for initializing the initial parameters, as well as the utilization of ciphertext values as feedback (perturbation) to update the Hénon Map parameters in each iteration. The proposed algorithm was evaluated using 25 test images in both grayscale and RGB formats. The experimental results achieved an average Shannon entropy value of 7.998, with differential sensitivity metrics reaching 99.606% for the Number of Pixels Change Rate (NPCR) and 33.464% for the Unified Average Changing Intensity (UACI). Meanwhile, the decryption process produced a Root Mean Square Error (RMSE) value of 0 and a Peak Signal-to-Noise Ratio (PSNR) of 100 dB. These findings indicate that the proposed architecture is capable of mitigating chaos degradation, resisting chosen-plaintext attacks, and reconstructing visual data without information degradation (lossless).